PHYTOCHEMICAL INVESTIGATION OF CHLOROFORM, DICHLOROMETANE AND ETHYL ACETATE EXTRACTS FROM THEFLOWERS OF ADENOCALYMMA IMPERATORIS-MAXIMILIANII (BIGNONIACEAE) - G. G. DE OLIVEIRA; J. A. DE S. PEREIRA JUNIOR; N. P. LOPES; S. J. DE MELO (International Journal of Pharma and Bio Sciences, 2014)
The Bignoniaceae family has 110 genera and approximately 650 species, widely distributed in tropical regions. Among the genera of this family, the Adenocalymma (46 species) have been little investigated from a phytochemical point of view, found only ethnobotanical reports. The aim of this study was the phytochemical characterization of chloroform, dichlorometane and ethyl acetate extracts from the flowers of Adenocalymma imperatoris-maximilianii (Wawra) L.G. Lohmann using analysis by GC-MS. Thirty-tree secondary metabolites were identified in ethyl acetate, twenty-eight in chloroform and thirty indichlorometane extracts from the flowers. There was evidence of Squalene in the ethyl acetate, chloroform and dichlometane extracts of this species. Due to the importance and the various biological activities described in the literature on compounds identified in this study A. imperatoris-maximilianii can be considered an alternative source of bioactive secondary metabolites for pharmaceutical therapy.